Synthesis of Enantiomerically Pure (S)-Methanocarbaribo Uracil Nucleoside Derivatives for Use as Antiviral Agents and P2Y Receptor Ligands - Melman, Artem (2008)
[Image: see text] We have developed an approach toward enantiomerically pure (S)-methanocarba ribonucleosides based on several functional group transformations on a sensitive bicyclo[3.1.0]hexane system. D-Ribose was transformed into methanocarba alcohol 3 followed by conversion of the OH group to a nitrile with inversion of configuration at C4. The nitrile group was subsequently reduced in two stages to the 5′-hydroxymethyl group. An ester group appended to a tertiary carbon (C1) was transformed to an amino group as a nucleobase precursor.